The Effect of Blended Project-based Learning Integrated with 21st-Century Skills on Pre-Service Biology Teachers' Higher-order Thinking Skills - Hujjatusnaini, N.; Corebima, A. D.; Prawiro, S. R.; Gofur, A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Educational institutions are required to prepare competent and competitive pre-service teacher graduates who have skills according to the needs of the 21st century. This study aims to find the effect of blended Project-Based Learning (PjBL) integrated with 21st-century skills on higher-order thinking skills of students as pre-service biology teachers on immunology. This research is an experimental study with a mixed method, in which the qualitative observation data used a questionnaire with self-assessment and peer assessment methods supported by experimental data using the HOTS instrument analyzed quantitatively. The application of blended PjBL integrated with 21st-century skills used a quasi-experimental research method with a quantitative descriptive approach. Pre-service teachers in this study are still studying at educational institutions, especially teacher faculty, and categorized as pre-service teachers. The research sample was students taking the immunology course in the Biology Education Study Program. They were 57 students from IAIN Palangka Raya, 60 students from Universitas Palangka Raya, and 83 students from Universitas Negeri Malang. Student grouping based on the initial ability of HOTS is carried out in all groups from which the student sample is referred to as a cluster. The total sample of 200 people was then grouped into three groups based on their basic abilities, namely low-level class, medium-level class, and high-level class. The study results proved that the blended PjBL integrated with 21st-century skills significantly affected students' high-level thinking skills based on the paired sample test (Sig. 2-tailed 0.0000.05). The mean value in the experimental group (75.53) and the control group (56.35) strengthens the data significance of students' higher-order thinking skills based on the N-Gain value and the independent sample T-test. The findings of this study are that blended PjBL integrated with 21st-century skills can increase HOTS on indicators of evaluating (78.15) and creating (79.21). This blended learning integration can be used as an innovative learning model solution to increase pre-service biology teachers' higher-order thinking skills according to the demands of 21st-century skills.